PEMBINAAN USAHA PENGRAJIN PAKAIAN ADAT LOMBOK MELALUI PELATIHAN MENENUN BERBASIS SYARIAH DAN TEKNOLOGI DIGITAL - Ahadiah Agustina; Abdul Wahab; Ageska Nugroho; Imam Mabrur (Universitas Muhammadiyah Kudus, 2025)
The traditional weaving industry in Sukarara Village, Lombok, holds significant economic and cultural potential. However, it faces various challenges, including a lack of innovation, limited market access, and insufficient understanding of Islamic economic principles in business management. This study aims to develop the potential of traditional clothing artisans in Lombok through Sharia-based and digital technology-driven weaving training. The research employs a qualitative approach, including field observations, in-depth interviews, and training sessions for artisans in Sukarara Village. The findings reveal that integrating Sharia-based training with digitalization enhances artisans' skills in design innovation, production efficiency, and marketing through digital platforms. Additionally, the Islamic economic approach fosters a better understanding of fair and transparent business practices, leading to sustainable economic improvements for the artisans. This study contributes to bridging the research gap regarding the application of Sharia principles in digital-based creative industries, particularly in the traditional weaving sector. Therefore, this training strategy is recommended for broader implementation to strengthen the competitiveness of local weaving industries in the global market.